Hexagonal Boron Nitride Growth on Cu‐Si Alloy: Morphologies and Large Domains. Issue 14 (5th March 2019) - Li, Jidong; Hu, Zhili; Yi, Yangfan; Yu, Maolin; Li, Xuemei; Zhou, Jianxin; Yin, Jun; Wu, Shiwei; Guo, Wanlin
Abstract: Controllable synthesis of high‐quality hexagonal boron nitride (h‐BN) is desired toward the industrial application of 2D devices based on van der Waals heterostructures. Substantial efforts are devoted to synthesize h‐BN on copper through chemical vapor deposition, which has been successfully applied to grow graphene. However, the progress in synthesizing h‐BN has been significantly retarded, and it is still challenging to realize millimeter‐scale domains and control their morphologies reliably. Here, the nucleation density of h‐BN on Cu is successfully reduced by over two orders of magnitude by simply introducing a small amount of silicon, giving rise to large triangular domains with maximum 0.25 mm lateral size. Moreover, the domain morphologies can be modified from needles, tree patterns, and leaf darts to triangles through controlling the growth temperature. The presence of silicon alters the growth mechanism from attachment‐limited mode to diffusion‐limited mode, leading to dendrite domains that are rarely observed on pure Cu. A phase‐field model is utilized to reveal the growing dynamics regarding B‐N diffusion, desorption, flux, and reactivity variables, and explain the morphology evolution. The work sheds lights on the h‐BN growth toward large single crystals and morphology probabilities. Abstract : Large domains of hexagonal boron nitride (h‐BN) are deposited on silicon‐doped Cu substrate. A rich variety of h‐BN domain morphologies can be delicately controlled through the growth temperature, from fractal tree patterns to dendritic triangles.